Validation of the Tool and Process of Testing Key Personnel, Talents and Potentials - Raspor, Andrej; Lacmanović, Darko; Mušinović, Fadil (Izzivi managementa talentov, 2025)
Successful organizations must have a system to identify key personnel, successors, and talents. Proper monitoring and testing are the most effective way to recognize these individuals. For testing tools to be effective, they need to be periodically validated. The usefulness of this research is evident from multiple perspectives. Evaluators will receive feedback on the testing tool itself and will be able to provide valuable input to the license owner, who can further improve the generic reports. With the gathered insights, the organization can enhance the overall process, particularly in the stages of personnel recruitment and feedback collection from leaders. Additionally, the validation process provides critical insights into the efficacy and accuracy of the testing tools, ensuring they remain relevant and reliable for future assessments. By refining these tools, organizations can better identify and develop their key personnel and successors, ensuring a robust talent pipeline. The continuous improvement of these processes will lead to more informed decision-making and a stronger alignment of talent management strategies with organizational goals. In conclusion, regular validation and improvement of testing tools and processes are essential for maintaining an effective system for identifying and nurturing key personnel.